2009
DOI: 10.1038/jcbfm.2009.253
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning Regulates Expression of microRNAs and a Predicted Target, MeCP2, in Mouse Cortex

Abstract: Preconditioning describes the ischemic stimulus that triggers an endogenous, neuroprotective response that protects the brain during a subsequent severe ischemic injury, a phenomenon known as 'tolerance'. Ischemic tolerance requires new protein synthesis, leads to genomic reprogramming of the brain's response to subsequent ischemia, and is transient. MicroRNAs (miRNAs) regulate posttranscriptional gene expression by exerting direct effects on messenger RNA (mRNA) translation. We examined miRNA expression in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
129
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(145 citation statements)
references
References 40 publications
13
129
1
2
Order By: Relevance
“…For example, one of the most notable downregulated miRNAs was miR-132, which regulates MeCP2 expression, a major regulator of gene expression. Consistent with the miRNA findings, MeCP2 protein expression was increased in the IPC brain and was required for ischemic tolerance, as knocking out MeCP2 expression in mice abrogated IPCmediated neuroprotection [62].…”
Section: Sumoylationsupporting
confidence: 73%
See 1 more Smart Citation
“…For example, one of the most notable downregulated miRNAs was miR-132, which regulates MeCP2 expression, a major regulator of gene expression. Consistent with the miRNA findings, MeCP2 protein expression was increased in the IPC brain and was required for ischemic tolerance, as knocking out MeCP2 expression in mice abrogated IPCmediated neuroprotection [62].…”
Section: Sumoylationsupporting
confidence: 73%
“…For example, Dharap and Vemuganti [61] found that 26 miRNAs were upregulated and 25 miRNAs downregulated in the rat cerebral cortex following IPC, with 20 of these miRNAs maintaining altered expression for 3 days. In the mouse cortex, Lusardi et al [62] compared miRNA expression from preconditioned and injurious ischemic groups, and found that miRNA expression is preferentially upregulated by IPC, but predominately downregulated by injurious ischemia. Bioinformatic analysis of miRNA expression revealed that IPC differentially regulates miRNAs that primarily target transcriptional regulators.…”
Section: Sumoylationmentioning
confidence: 99%
“…26 In cerebral ischemic models, a few studies have profiled the broad miRNA changes in the ischemic brain and blood and provided novel mechanical insights and therapeutic targets. 6,7,27 In contrast, our study focused at the direct identification of neuroprotective miRNAs in the early IPC model at 3 hours after the brief ischemia and thus could suggest selective miRNAs involved in neuroprotection. Because our analysis used only cortical ischemic tissues influenced by IPC, our miRNA profiles were predesignated to the IPC study and the observed profiles in our ISC groups may be different from the previous observations that examined the entire ischemic hemisphere.…”
Section: Lee Et Al Micrornas In Ischemic Preconditioningmentioning
confidence: 99%
“…The knockdown of miR-497 enhances the Bcl-2/-w expression, showing that miR-497 exerts the role of apoptosis by repressing Bcl-2/-w in the pathogenesis of ischemic brain injury (22). Lusardi et al (20) revealed that miR-132 directly regulates methyl-CpG binding protein 2 (MeCP 2 ) protein expression that acts as an effector of IP-induced tolerance in rat cortical neurons. Lee et al (19) found that the miR-200 family decreased the expression of prolyl hydroxylase 2 (PHD2), but increased the levels of hypoxia-inducible factor 1 (HIF-1) in Neuro-2a cells, suggesting that the miR-200 family have a neuroprotective effect by mainly reducing PHD2 as a post-translational regulator of HIF during hypoxia.…”
Section: Cerebral Ischemiamentioning
confidence: 99%